New taxa of the family Syringophilidae (Acari: Prostigmata) from African barbets and woodpeckers (Piciformes: Lybiidae, Picidae) - Skorack, Maciej; Klimovičová, Miroslava; Muchai, Muchane; Hromada, Martin (Zootaxa, 2014)
New taxa of quill mites (Acari: Syringophilidae) are described from African barbets and woodpeckers in the Ethiopian region. A new monotypic genus Picineoaulonastus gen. nov. is established for a new species Picineoaulonastus pogoniulus sp. nov., parasitising 2 lybiid species, Pogoniulus bilineatus (Sundevall) (type host) in Kenya and Tanzania and P. pusillus (Dumont) (Piciformes: Lybiidae) in Ethiopia. Additionally, 2 more new syringophilid species are described: Neosyringophilopsis lybidus sp. nov. from P. bilineatus in Kenya, and Syringophiloidus picidus sp. nov. from Dendropicos fuscescens (Vieillot) (Piciformes: Picidae) in Kenya, Uganda, and Tanzania.